The Relationship between Socioeconomic Status and Adherence to Antihypertensive Treatment Regimen in a Metropolitan Community Sample of Hypertensive African Americans in New York - Ednah Madu,; Kingsly Madu, (Public Health, 2019)
IntroductionLow socioeconomic status (SES) is one of the strongest predictors of morbidity and premature mortality worldwide, as well being associated with large increases in cardiovascular disease in both men and women. Uncontrolled hypertension contributes to cardiovascular disparity. Non-adherence to antihypertensive regimens worsens the cardiovascular burden and further widens the health disparity gap. A hierarchical multiple regression study of multiple factors impacting adherence among urban residents in a New York metropolitan region found socioeconomic factors as the strongest factors impacting adherence in this cardiovascular high-risk population..MethodsSecondary analysis of data of a cross-sectional, correlation design study of a dissertation study, with each of the SES variables analyzed against adherence and self-efficacy variables. ResultsOverall, only three SES variables (years with the same provider, work status and income) were significantly related to adherence and/or self-efficacy. Years with the same provider was related to adherence with correlation of rs=0.16 (p=0.048), and to self-efficacy rs=2.0 (p=0.016). Work status was related to adherence with difference in adherence scores between retired and unemployed subjects (KS=38.6, p=0.013 with Bonferroni adjustment; means=3.7 and 3.3, respectively). Work status was not related to self-efficacy scores. Income level was significantly related to the self-efficacy scores, but not the adherence scores. Difference noted between earners<$10,000/year and >$80,000/year (KS=-44.2, p=0.037, with Bonferroni adjustment; means=3.06 and 3.51, respectively). DiscussionLow socioeconomic status and non-adherence to antihypertensive regimens remain important factors which worsen cardiovascular health and widen health disparity health gaps. This is evident among the cardiovascular high-risk persons of African descent including those residing in the New York metropolitan regions. Self-efficacy is implicated as a mediating variable between income and adherence. The inverse relationship between fulltime work status and adherence was no longer noted. Further investigation on the associations between income, full time status and adherence among young, hypertensive Blacks/African Americans; as well as self-efficacy mediating effects on income and adherence is recommended.